GAYA HIDUP THIRFTING DI PASAR LERENG BUKITTINGGI : STUDI KHASUS MOTIVASI FASHION DAN KEPUASAN ANAK MUDA - Elviriani Br Sitepu; Basyarul Aziz; Esa Rahmadani (STKIP Subang, 2026)
The thrifting phenomenon at Pasar Lereng Bukittinggi has undergone a shift in meaning, from a mere economic solution to a lifestyle representing the social identity and creativity of young people. This study aims to analyze fashion motivation and consumer satisfaction among youth (specifically university students and Gen Z) through second-hand clothing consumption. Using a descriptive qualitative method, data were collected through observation and in-depth interviews with six informants, including traders and active consumers. The analysis employed three Contemporary Anthropology theories: Georg Simmel's Fashion theory to dissect identity motivation, Arjun Appadurai’s